The influense of neuro-aids in children - Capelo, Albertina V; Sá, Carlos Alberto M; Rubini, Norma P; Kalil, Rosangela S; Miranda, Eliane (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the influence of the infection of the central nervous system in the neurodevelopment of the child infected with HIV-1 deserves better understanding.Objective: to evaluate neurological disorders in HIV-1 infected children and possible associated factors. Methods: review of more than 100 papers publishedrecently in national and international medical literature concerning neuropathogenesis of AIDS and its influence in the neurological development of HIVinfected children. Results: HIV-1 invades the central nervous system (CNS) early in infection and is the first AIDS-defining illness in as many as 18% ofpediatric patients. In the neuropathogenesis of AIDS in children we must stress the viral interactions with astrocytes. Differences in the level of proinflammatorymediators in the cerebrospinal fluid (CSF), and the productive infection of neurons are the main differences in children. The reported prevalence of delay inneurodevelopment among HIV-infected children has varied from 8% to more than 60%. An increased prevalence is associated with the severity of theinfection, increasing age, but also occur with children with efficient HAART regimens. Papers selected have distinct conclusions in relation to the risk factorsassociated with neurodevelpmental delays of HIV infected children. Conclusion: the molecular and cellular mechanisms of the neuropathogenesis of HIV-1infection are extremely complex and not well understood. Neurodevel pmental delay is clearly associated with HIV-1 infection in children and can be animportant indicator of the infection evolution. It is essential to idenfity, using neurodevelopmental assessment tools, early warning signs of HIV-1 associatedneurological disorders in infected children.